The Co-production of Archaeological Knowledge: The Essential Relationship of Amateurs and Professionals in 20th Century American Archaeology - Christenson, Andrew L. (Complutum, 2013)
The process of professionalization in American archaeology naturally created boundaries between insiders and outsiders, with insiders having special training or degrees and institutional affiliation and employment. Amateur archaeologists, with their intimate knowledge of sites and the landscapes into which they are situated, were actively involved in trying to understand the archaeological record but were often treated as outsiders even though their insights were critical to archaeological understanding. Unfortunately, some historians of the field have taken such boundary work by professionals as given, thus writing out an important group of archaeological researchers. Using selected examples, this paper suggests the concept of “co-production of knowledge” as a useful way of thinking about the interaction of amateurs and professionals.